Distribution of peroxidase activity and polyamine pattern of Heliotropium europeum in potassium deficiency conditions - Palavan Ünsal, Narçin; Ansan, Elif Damia (INDERSCIENCE ENTERPRISES LTD, WORLD TRADE CENTER BLDG, 29 ROUTE DE PRE-BOIS, CASE POSTALE 896, CH-1215 GENEVA, SWITZERLAND, 2007)
Polyamines, especially putrescine, are reported to increase in higher plants in response to various stressors, in particular mineral deficiency, low pH and different atmospheric pollutants. Peroxidases are another stress indicator in plants. The aim of this study is to establish the relationship between polyamine content and peroxidase activity in potassium deficiency conditions. In this study, potassium deficiency increased the free and bound Put and Spd contents. We estimated more stimulation in free Put synthesis (300%) in potassium deficiency. We also determined increment in POD activity in whole plant, especially root POD activity increased much more compared to stem and leaf.
Keywords: polyamines; potassium deficiency; putrescine; peroxidase; induced proline accumulation; rape leaf discs; oryza-sativa-l; salt tolerance; putrescine; seedlings; stress; tomato; plants; adjustment; poliaminler; potasyum eksikliği; peroksidaz; kaynaklı prolin birikimi; tuz toleransı; fidan; stres; domates; bitkiler; ayarlama